2015
DOI: 10.1186/s12936-015-0871-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation of malaria entomological parameters at the onset of a hydro-agricultural development in central Côte d’Ivoire

Abstract: BackgroundA deeper understanding of the ecology and small-scale heterogeneity of malaria transmission is essential for the design of effective prevention, control and elimination interventions. The spatial and temporal distribution of malaria vectors was investigated in five villages in close proximity to a hydro-agricultural system in Côte d’Ivoire over the course of construction and the early phase of irrigated rice farming.MethodsThe study was carried out in five villages (Raffierkro, N’Douakro, Ahougui, Kp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
(27 reference statements)
4
21
0
Order By: Relevance
“…collected exhibited high parity rates in all districts, thus suggesting that a signi cant proportion of the local vector populations that have su cient lifespan allowing for the completion of Plasmodium parasite lifecycle and transmission to humans. Similar ndings have previously been reported in Côte d'Ivoire [46,48].…”
Section: Discussionsupporting
confidence: 92%
“…collected exhibited high parity rates in all districts, thus suggesting that a signi cant proportion of the local vector populations that have su cient lifespan allowing for the completion of Plasmodium parasite lifecycle and transmission to humans. Similar ndings have previously been reported in Côte d'Ivoire [46,48].…”
Section: Discussionsupporting
confidence: 92%
“…coustani (0.27%) were higher in non-irrigated than irrigated village (nil for all species). Similar to our results, various studies indicated the presence of signi cantly higher annual sporozoite rate in non-irrigated than irrigated villages in different parts of Africa [5,81,112,113]. Ijumba et al [112], Appawu et al [5], and Sogoba et al [114] also reported highest annual sporozoite rates for An.…”
Section: Discussionsupporting
confidence: 90%
“…Ahougui, Koffikro, Kpokahankro, N’Douakro and Raffierkro) [18] and two villages without activities in proximity to the small dam (i.e. Mamian and N’Drikro).…”
Section: Methodsmentioning
confidence: 99%